ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN MASALAH MATEMATIKA BERUPA SOAL PADA FASE E DI SMA NEGERI 3 PADANG BERDASARKAN ANALISIS NEWMAN - AN NISAH, AULIYA (Jurnal Edukasi dan Penelitian Matematika, 2023)
Math is a subject that has evolved and helps high school students solve problems. Many still make mistakes when solving these situations. Their math errors are the focus of this study. A descriptive qualitative type was conducted, by collecting data using problem-solving skills questions and unstructured interviews. Class X E 7 SMA Negeri 3 Padang. Many errors in solving Newman analysis-based problems, according to this study. namely errors (1) reading the problem by 17%; (2) understanding the problem by 25%; (3) transforming the problem by 30%; (4) process skills by 56%; (5) writing the final answer by 71%. The fifth skill was performed by subjects with high problem solving ability. While the medium ability made mistakes in three stages. Subjects with low problem solving ability made errors in understanding, transforming, processing, and writing answers. Keywords– Nerman Error Analysis, Sequences and Series, Problem Solving Ability